Gynecologic cancer in perimenopause - Valdivieso, Roger (2015)
OBJECTIVE: To determine the frequency of gynecological cancer during perimenopause, and then establish which types of cancer can benefit with cancer screening. MATERIAL AND METHODS: Age andfrequency oftervix, breast, ovary, endometrium and vulvar cancer were determined inpatients between 45 and 50 years at Guillermo Almenara Hospital. RESULTS: Mammarian and ovarian cancer were diagnosed predominantly during the Perimenopause and cervical cancer was diagnosed 5 years later. In thepostreproductive period the agefrequency of cervical, mammary and ojorumv cancer were 64,5%, 63,6%; and 64,3%, respectively. Endometrium cancer was diagnosed one decade later. All patients with vulvar cancer (100%) were posmenopausal. CONCLUSION: Gynecological cancer must be diagnosed during the perimenopause when consultation about climacteric symptoms increase.